Laboratory tests, numerical simulations and design of austenitic stainless steel semi-oval hollow section columns - Li, Shuai (2024)
Semi-oval hollow section is an innovative cross-section profile and consists of one semi-circular flange, one flat flange and two flat webs. While the semi-circular flange (exposed to fluid or wind) offers a low level of hydrodynamic or aerodynamic drag, the flat elements facilitate connections with other members. The flexural buckling behaviour and resistances of austenitic stainless steel semi-oval hollow section columns are investigated in this paper. An experimental programme was firstly conducted on two austenitic stainless steel semi-oval hollow sections, with six column specimens of varying member lengths adopted for each cross-section, and included tensile coupon tests, initial geometric imperfection measurements and pin-ended column tests. Both ‘C’-shaped flexural buckling (with failure specimens bowing towards semi-circular flanges) and ‘reverse C’-shaped flexural buckling (with failure specimens bowing towards flat flanges) were observed upon testing. The experimental programme was accompanied by a numerical modelling programme, with finite element models developed to simulate the test results and then adopted to conduct parametric studies to generate further numerical data. On the basis of the test and numerical data, the relevant buckling curves for austenitic stainless steel circular hollow section columns, as provided in the European code, American specification and Australian/New Zealand standard, were evaluated for their applicability to austenitic stainless steel semi-oval hollow section columns. The evaluation results generally revealed that the codified buckling curves led to overall accurate and consistent flexural buckling resistance predictions when used for austenitic stainless steel semi-oval hollow section columns.